The role of sports physicians in doping: A note on incentives - Evelyn Korn; Volker Robeck (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
How to ban the fraudulent use of performance-enhancing drugs is an issue in all professional - and increasingly in amateur - sports. The main effort in enforcing a clean sport has concentrated on proving an abuse of performance-enhancing drugs and on imposing sanctions on teams and athletes. An investigation started by Freiburg university hospital against two of its employees who had been working as physicians for a professional cycling team has drawn attention to another group of actors: physicians. It reveals a multi-layered contractual relations between sports teams, physicians, hospitals, and sports associations that provided string incentives for the two doctors to support the use performance-enhancing drugs. This paper argues that these misled incentives are not singular but a structural part of modern sports caused by cross effects between the labor market for sports medicine specialists (especially if they are researchers) and for professional athletes.
Keywords: 330